Bioterrorism in Canada: An Economic Assessment of Prevention and Postattack Response - Ronald St John; Brian Finlay; Curtis Blair (Canadian Journal of Infectious Diseases)
The present paper calculates the human and economic consequences of a bioterrorist attack on Canadian soil using aerosolized Bacillus anthracis and Clostridium botulinum. The study assumed that 100,000 people in a Canadian suburban neighbourhood were exposed over a 2 h period to an infectious dose of one of the agents. Using an epidemic curve based on the epidemiology and management of anthrax and botulinum poisoning, the costs of intervention and treatment after an attack were compared with the costs of preparedness before a bioterrorist attack. The results show that an investment in planning and preparedness to manage the consequences of an attack can reduce morbidity, mortality and economic costs. The sooner that an intervention program is instituted, the more significant are the health and economic benefits. The greatest benefits were realized when postattack intervention was initiated before day 3 after the event. The economic impact of a bioterrorist attack in Canada could range from $6.4 billion/100,000 exposed to B anthracis to $8.6 billion/100,000 exposed in an attack using C botulinum. Without the benefit of an effective consequence management program, predicted deaths totalled 32,875 from anthrax and 30,000 from botulinum toxin. Rapid implementation of a postattack prophylaxis program that includes the stockpiling of antibiotics, vaccines and antitoxins; training of first responders in the diagnosis, handling and treatment of pathogens; and the general enhancement of Canada's response capability would reduce both human and economic losses.